NHC‐Stabilized Nickel Olefin, Dialkyl, and Dicyanido Complexes. Issue 26 (4th July 2019) - Berthel, Johannes H. J.; Tendera, Lukas; Kuntze‐Fechner, Maximilian W.; Kuehn, Laura; Radius, Udo
Abstract : The complexes trans‐ [Ni( i Pr2 Im)2 Br2 ] 1, trans ‐[Ni( i Pr2 Im Me )2 Br2 ] 2, trans ‐[Ni(Me2 Im)2 I2 ] 3, and trans ‐[Ni(Me2 Im Me )2 Br2 ] 4 (R2 Im = 1, 3‐diorganyl‐imidazolin‐2‐ylidene, R2 Im Me = 1, 3‐diorganyl‐4, 5‐dimethyl‐imidazolin‐2‐ylidene) are useful precursor for the synthesis of NHC‐stabilized nickel olefin, alkyne, alkyl and cyanido complexes. [Ni(NHC)2 (η 2 ‐olefin)] and [Ni(NHC)2 (η 2 ‐alkyne)] can be prepared via metallic reduction in the presence of the olefin or alkyne, as exemplified by the synthesis of [Ni(Me2 Im)2 (η 2 ‐C2 H4 )] 5, [Ni(Me2 Im)2 (η 2 ‐C2 Me2 )] 6, [Ni(Me2 Im)2 (η 2 ‐COE)] 7 and [Ni(Me2 Im Me )2 (η 2 ‐COE)] 8 (COE = cyclooctene). The reaction of trans ‐[Ni( i Pr2 Im Me )2 Br2 ] 2 with MeMgCl, EtMgBr or n BuLi leads to trans ‐[Ni( i Pr2 Im Me )2 (CH3 )2 ] 9, trans ‐[Ni( i Pr2 Im Me )2 (C2 H5 )2 ] 10 and trans ‐[Ni( i Pr2 Im Me )2 ( n ‐C4 H9 )2 ] 11 . The reaction of 2 with i PrMgBr afforded minor amounts of [Ni( i Pr2 Im Me )2 (η 2 ‐H2 C=CHCH3 )] 12 . Dicyanido complexes trans ‐[Ni( i Pr2 Im)2 (CN)2 ] 13, trans ‐[Ni( i Pr2 Im Me )2 (CN)2 ] 14, trans ‐[Ni(Me2 Im)2 (CN)2 ] 15, and trans ‐[Ni(Me2 Im Me )2 (CN)2 ] 16 were prepared from reaction of the dihalide complexes 1 –4 and trimethylsilyl cyanide. Abstract : The synthesis of different NHC‐stabilized nickel olefin, alkyne, alkyl, and cyanido complexes is reported starting from trans‐ [Ni( i Pr2 Im)2 Br2 ], trans ‐[Ni( i Pr2 Im Me )2 Br2 ], trans ‐[Ni(Me2 Im)2 I2 ], and trans ‐[Ni(Me2 Im Me )2 Br2 ] (R2 Im = 1, 3‐diorganyl‐imidazolin‐2‐ylidene, R2 Im Me = 1, 3‐diorganyl‐4, 5‐dimethyl‐imidazolin‐2‐ylidene) as synthetically useful nickel (II) precursors.